(untitled) (Research, Society and Development, 2023)
An athlete needs to have their overall health in optimal condition to compete at the highest level, and oral health is essential for such condition. It is known that periodontal disease is highly prevalent in the population, and acidic salivary pH directly influences oral health conditions, potentially leading to various oral problems. This study aimed to assess the behavior of salivary pH in athletes with active periodontal disease and after its remission. The selected volunteers with periodontal disease underwent oral hygiene instruction and basic periodontal therapy and were reevaluated after 30 days. Periodontal markers were used through Basic Periodontal Examination to determine the presence and progression/regression of periodontal disease. Saliva samples were also collected at the initial appointment and during the follow-up visits for salivary pH comparison. The results showed initial oral acidity that moved towards neutrality after treatment. The Friedman test (analysis of variance for repeated measures by ranking) was used. The non-parametric test for differences between repeated measures yielded a Chi-Square value of 16.647, considered statistically significant (p < 0.001). The presente study concludes that periodontal disease in high-performance athletes influences salivary pH behavior.